Letramento escolar: eventos e apropriações de gêneros textuais por adolescentes - Valeria Barbosa de Resende (2011)
The objective of this paper is to analyze the situation of teenagers enrolled on the third cycle with insufficient development of the reading and writing skills. It intends to describe and analyze events and practices of literacy at school, substantiating the written productions done in the classroom, as well as the process of appropriation of genders and textual types by the adolescents. This research is included in studies about literacy at school and discursive genders, assuming as a theorical perspective in its social and dialogical nature, produced as human actions (BAKHTIN, 2003; STREET, 1984 and 2003; SOARES, 2003 and 2004; KLEIMAN, 1995; SCHNEUWLY e DOLZ, 2004; ROJO, 1998 and 2009 and RIBEIRO, 1999 e 2003). The research was done between March and December 2007 and followed the work developed by a teacher and 42 adolescents between the age of 12 and 17, in the project entitled Rede do 3º Ciclo, organized by the Secretaria Municipal de Educação de Belo Horizonte, Minas Gerais, whose goal was to create real dialogue channels between literacy at school and these young adolescents culture, allowing their inclusion in the practice at school. A quantitative methodology, with a combination ethnographic inspiration was used, with the intention of uncovering the internal knowledge in the context of the experiences in the classroom (GREEN, DIXON, ZAHARLICK, 2005; CASTANHEIRA, 2004 e RAYOU, 2005). By the participating observation five literacy events were organized, substantiating the actions developed by the teacher and by the teacher at the moment of the textual production, and highlighting the ways these genders were read and produced in class (taught literacy practices). In the events analysis a pattern procedure was verified in the teachers actions: she offers a model of the textual gender before asking for a production; allows the return of the produced text, revised by the teacher, by reading, in class; and socializes the production through a board or binding the texts, available in the classroom library. Considering the data gathered in the focal group and interviews, the following were analyzed: the adolescents statements about the text genders taught and their appropriation processes, besides the analyses of the social uses of reading and writing (acquired literacy practices). It was verified that the teenagers carried out the scenes at school when they modified the solicited textual gender (from ads to jokes, for example) and when the used drawings to mold the discourse. On the other side they were confronted with the ideology present in the school discourse (in the drawing censorship and the words used when writing notes, for example). In this analysis it was possible to see that it is necessary to invest in pedagogical proposals which try to establish a dialogue between literacy at school and the adolescents culture, to raise the literacy level and generate positive results in the national and international evaluations, which, despite considering only one type of literacy, allows the adolescents to be included in different contexts in a critical and protagonist way.